MiR-657 Promotes Macrophage Polarization toward M1 by Targeting FAM46C in Gestational Diabetes Mellitus. (13th December 2019) - Wang, Pingping; Wang, Zengfang; Liu, Guojie; Jin, Chengwen; Zhang, Quan; Man, Shuhong; Wang, Zengyan
Abstract : MicroRNA (miRNA) has been widely suggested to play a vital role of in the pathogenesis of gestational diabetes mellitus (GDM). We have previously demonstrated that miR-657 can regulate macrophage inflammatory response in GDM. However, the role of miR-657 on M1/M2 macrophage polarization in GDM pathogenesis is not clear yet. This study is aimed at elucidating this issue and identifying novel potential GDM therapeutic targets based on miRNA network. miR-657 is found to be upregulated in placental macrophages demonstrated by real-time PCR, which can enhance macrophage proliferation and migration in vitro. Luciferase reporter assay shows the evidence that FAM46C is a target of miR-657. In addition, miR-657 can promote macrophage polarization toward the M1 phenotype by downregulating FAM46C in macrophages. The present study strongly suggests miR-657 is involved in GDM pathogenesis by regulating macrophage proliferation, migration, and polarization via targeting FAM46C. miR-657/FAM46C may serve as promising targets for GDM diagnosis and treatment.